Original Statement: If x = 3, then x^2 = 9 (true)
Converse: If x^2 = 9, then x = 3 (false; this is half the story and x = -3 must be included)
Since the converse isn't completely true, we can't combine the two statements to get a biconditional.
A is correct because f(1)=3^1+1 so f(1)=4 and g(x)=4 so f(x)=g(x)
B is also correct because the ordered pair we get is (1,4) and this is in quadrant 1
C is incorrect
D is incorrect
E is incorrect
Ans: A and B are correct
it's either a or b, not sure but I think it's b
The answer i got was -3te with -t as an exponent